Varicella Zoster Virus Meningitis in a Young Immunocompetent Adult without Rash: A Misleading Clinical Presentation - Thomas Pasedag; Karin Weissenborn; Ulrich Wurster; Tina Ganzenmueller; Martin Stangel; Thomas Skripuletz (Case Reports in Neurological Medicine)
Meningitis caused by varicella zoster virus (VZV) is rare in healthy population. Predominantly immunocompromised patients are affected by reactivation of this virus with primary clinical features of rash and neurological symptoms. Here we report a young otherwise healthy man diagnosed with a VZV meningitis without rash. He complained of acute headache, nausea, and vomiting. The clinical examination did not show any neurological deficits or rash. Cerebrospinal fluid (CSF) analysis revealed a high leukocyte cell count of 1720 cells/µL and an elevated total protein of 1460 mg/L misleadingly indicating a bacterial infection. Further CSF analyses, including polymerase chain reaction (PCR) and detection of intrathecal synthesis of antibodies, showed a VZV infection. Clinical and CSF follow-up examinations proved the successful antiviral treatment. In conclusion, even young immunocompetent patients without rash might present with VZV meningitis. CSF examination is a key procedure in the diagnosis of CNS infections but in rare cases the standard values cell count and total protein might misleadingly indicate a bacterial infection. Thus, virological analyses should be considered even when a bacterial infection is suspected.